Dynamic Demand Control of 3.5MW Solar LG Plant Using Zero Export Device - Shekhawat, Kamal Singh (My University, 2022)
Recently, photovoltaic (PV) panels as part of renewable energy sources are being used in many systems. With the rapid growth of photovoltaic system connections to power networks, the development of efficient interfacing grid metals has become increasingly important for photovoltaic systems to ensure zero export. This study and work introduces the operating system, control system and flexible response of the zero export system designed for the Grid-PV system, to demonstrate the accuracy and capability of the device presented with a commercial grid-tie inverter. Solar photovoltaic energy (PV), or solar energy capture by photovoltaic panel to generate electricity, is considered one of the most promising markets renewable energy portfolio, due to its ability to reduce global warming and convergence CO2 reduction targets set by international governments and international agreements. The PV industry has grown almost steadily in recent years, as shown by increasing production capacity and growing networks of solar suppliers and funding systems worldwide.
Keywords: Zero Export Device; renewable energy sources